Pengaruh Pandemi Covid-19 Terhadap UMKM Di Kota Bandung - Windi Satariah Windi (EKBIS (Ekonomi & Bisnis), 2021)
The purpose of this study is to examine the effect of the Covid-19 pandemic and the survival strategies of business actors. Business actors as drivers of the economy have challenges due to government regulations regarding the limitations of community mobility. This research is based on data from news about SMEs in the city of Bandung. The number of business actors in Bandung is the data used. This study uses a descriptive qualitative approach by using literature studies and interviews from various sources. The impact felt by business actors during this covid pandemic is reduced sales and decreased income. Various efforts have been made by business actors to adapt to the current situation, among others, by moving the sales method using online. Indirectly, business actors get new insights about digitizing sales. From the results of this study, MSMEs can still survive during this pandemic by following online sales strategies and digitizing their sales system. Keyword : MSMEs, Covid-19, Digitalization, Pandemic